Efficacy and safety of second-line therapy by S-1 combined with sintilimab and anlotinib in pancreatic cancer patients with liver metastasis: a single-arm, phase II clinical trial - Qiu, Xin; Lu, Changchang; Sha, Huizi; Zhu, Yahui; Kong, Weiwei; Tong, Fan; Wang, Qiaoli; Meng, Fanyan; Liu, Baorui; Du, Juan (Frontiers in Immunology, 2024)
Background: Pancreatic adenocarcinoma carries a grim prognosis, and there are few recognized effective second-line treatment strategy. We attempted to evaluate the efficacy and safety of a combination of S-1, Sintilimab and Anlotinib as a second-line treatment in pancreatic cancer patients with liver metastasis.Methods: Pancreatic cancer patients with liver metastases were recruited. S-1 was administered orally at 25 mg/m 2 bid and Anlotinib was administered orally at 12 mg qd from day 1 to day 14, Sintilimab was administered intravenously at 200 mg on day 1. This method was repeated every 21 days and the therapeutic effect was evaluated every 3 cycles. The primary outcome was objective response rate (ORR).Results: Overall, 23 patients were enrolled in this study of whom 19 patients had objective efficacy evaluation. The ORR was 10.5% (95%CI 0.4-25.7%) in the evaluable population. The progression-free survival (PFS) were 3.53 (95%CI 2.50-7.50) months and overall survival (mOS) were 8.53 (95%CI 4.97-14.20) months.Grade 3 adverse events were 26.1%, and no grade 4 or above adverse events occurred.The tumor tissues of 16 patients have done high-throughput sequencing, patients with HRD-H (n=10) had shorter PFS than those with HRD-L (n=6) (2.43 vs. 5.45 months; P = 0.043), but there was no significant difference in OS between the two groups (4.43 vs. 9.35 months; P = 0.11).This study suggests that the advantage of S-1 combined with Sintilimab and Anlotinib in extending OS as second-line therapy in pancreatic cancer patients with liver metastasis.